Critical Analysis of Indonesia’s Foreign Policy in Global Politics - Jerry Sambuaga (International Forum of Researchers and Lecturers, 2025)
Indonesia's foreign policy has become a topic of interest to many parties in recent years. In the context of increasingly complex global politics, Indonesia needs to have an effective foreign policy to strengthen its role within the international community. This study aims to critically analyze Indonesia's foreign policy in global politics. This study uses a qualitative approach with a critical analysis of Indonesia's foreign policy. The results of the study show that Indonesia's foreign policy has undergone significant changes in recent years, but there are several challenges that still need to be addressed. This study also shows that Indonesia needs to enhance its role in the international community through an effective foreign policy.